Corporate social responsibility and independent employee representation: an ethical contradiction?. Issue 3 (30th November 2020) - Ryan, Lorraine; Turner, Thomas
Abstract : Purpose: Many familiar global corporations have well-developed corporate social responsibility (CSR) policies that enunciate socially caring values that include the dignity and well-being of their employees. Yet opposition to independent employee voice from companies with trumpeted CSR credentials indicates an uncomfortable contradiction between rhetoric and reality in the treatment of employees as valued stakeholders. The purpose of this paper is to explore these contradictions using the lens of a libertarian tradition. Design/methodology/approach: The CSR statements of three companies are examined to provide the context for their espoused values towards employees. Media, trade union and academic publications on each of the companies are then considered to identify systematic evidence of anti-union practices. Findings: The paper illustrates the paradox of companies with espoused CSR policies advocating the dignity and well-being of their employees with often explicit coercive anti-union practices. These practices are a constraint on the negative freedom/liberty of employees in the libertarian tradition and amount to unethical behaviour on the part of the firm. Originality/value: The paper offers important insights into the disconnection common in many firms between normative ethical claims in CSR statements to treat employees as valued legitimate stakeholders and the reality in the workplace.